ORGANIZATION OF CONNECTION OF BANK – INSURANCE COMPANY AS METHOD OF MANAGEMENT OF ORGANIZATIONAL RISK (FOR EXAMPLE OF RUSSIA AND ARMENIA) - Arthur Volodyevich Poghosyan (Вестник Северо-Кавказского федерального университета, 2022)
The article presents the trends of development of the banking and insurance markets of Russia and Ar- menia are presented. Processes of bank loans and pledge insurance under the loan are considered. The model of remote insurance of pledge and ways of automation is offered.